Габітарний імідж IT-фахівця: особливості та складники - Постельник, А. С. (ХНУРЕ, 2025)
The habitus image is an important component of a modern specialist's professional image, encompassing both external and internal characteristics. This is especially relevant in the IT field, where competition is high, and success depends not only on technical knowledge but also on the ability to make a positive impression. A well-crafted habitus image helps build trust, demonstrate professionalism, and facilitate effective communication within teams and with clients. It involves a harmonious combination of appearance, behavior, and communication style, contributing to a specialist's overall reputation and career growth.
Keywords: імідж IT-фахівця; габітарний імідж